O processo de geração de conhecimento em empresas multinacionais para a criação de produtos e serviços - Pinto, Márcia Cristina Vieira (2009)
The present study has focalized the enterprises knowledge process to create products and services, in multinational corporations. We have begun from the hypothesis that the information and knowledge are the largest weapons in the generation of products and differentiated services and factor of high competitiveness for the companies in global scenery. We believed that the differential competitive of the companies it is based on explicit knowledge, provide by information databases and their professionals tacit knowledge and that the business success is now sustained by the existence of organizational internal conditions that motivate and support the sharing of those knowledge. In multinational corporations, the process of knowledge generation has already been worked there are decades for experienced professionals, processes, technologies and tools. The idea that the post-modern society is founded on the science and the information and the business world is fundamentally based on the intellectual capital and in their capacity of knowledge generation contribute to actual scenery, where countless economical historical events, strongly leaning for the intensive use of several technologies and the Internet, created a demand for capable professionals to capture or to produce information, to extract meaning from them and with that to make decisions and solve complex problems in the global scenery. As backdrop of the business scenery appears what many authors call of Society of the Knowledge or Society of the Information , characterized by the crescent job of the knowledge as input for the development of products and services and as decisive factor of success for the survival of the companies in a competitive market. The resources information and knowledge started to be more than considered never noble for the companies and capable professionals act in the process of knowledge generation to leave of those resources they started to have great value for that market. To treat the subject, we defined the following analysis points that we considered important for the development of this dissertation: (a) Reflections on current business context and the implication in the professional world. (b) Information and knowledge used in the multinational enterprises. (c) the technology as a tool that support the construction of the knowledge. (d) Identification of approaches for the construction of the knowledge in the multinational enterprises. The analyses took us to the conclusion that the multinational enterprises, as a way to survive, must continue learning and they depend more and more on the resources of information, knowledge and, above all, of people capable to operate that transformation